2022
DOI: 10.3390/antiox11091774
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Fumarate (DMF) Alleviated Post-Operative (PO) Pain through the N-Methyl-d-Aspartate (NMDA) Receptors

Abstract: The management of post-operative (PO) pain has generally been shown to be inadequate; therefore, acquiring a novel understanding of PO pain mechanisms would increase the therapeutic options available. There is accumulating evidence to implicate N-methyl-d-aspartate (NMDA) receptors in the induction and maintenance of central sensitization during pain states by reinforcing glutamate sensory transmission. It is known that DMF protects from oxidative glutamate toxicity. Therefore, NMDA receptor antagonists have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Therefore, considering the notable role played by the p-IKBα-NF-kB pathway in the devel-opment of chronic pain and mood disorders, our data suggest that the normalization of the overexpression of p-IKBα in the DRG and HIP produced by UFP-512 might be involved in the inhibition of allodynia as well as of the emotional and/or mechanical deficits produced by this DOR agonist. In accordance with this suggestion, other treatments such as berberine and dimethyl fumarate also relieve gouty arthritis, neuropathy or post-operative pain by blocking the activation of p-IKBα-NF-kB pathway [59][60][61].…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, considering the notable role played by the p-IKBα-NF-kB pathway in the devel-opment of chronic pain and mood disorders, our data suggest that the normalization of the overexpression of p-IKBα in the DRG and HIP produced by UFP-512 might be involved in the inhibition of allodynia as well as of the emotional and/or mechanical deficits produced by this DOR agonist. In accordance with this suggestion, other treatments such as berberine and dimethyl fumarate also relieve gouty arthritis, neuropathy or post-operative pain by blocking the activation of p-IKBα-NF-kB pathway [59][60][61].…”
Section: Discussionmentioning
confidence: 94%
“…The neuroprotective effects of DMF in neurodegenerative disorders [7], as well as in osteoarthritis pain, post-operative pain, and neuropathic pain caused by spare nerve injury or by chemotherapeutic agents, have been demonstrated [22,23,39,40]. Other studies also revealed that another Nrf2 activator, sulforaphane, as well as the HO-1 inducer, CoPP, both inhibited neuropathic pain provoked by CCI or associated with diabetes [24,25,41,42] and inflammatory pain caused by CFA injection [27].…”
Section: Discussionmentioning
confidence: 95%
“…Transforming growth factor β (TGF-β), an important profibrotic growth factor and vascular endothelial growth factor (VEGF), a key angiogenic mediator of pulmonary fibrosis were determined by immunohistochemistry in lung tissues as previously described [ 33 ]. Lung sections were incubated overnight with anti-TGF-β (Santa Cruz Biotechnology; 1:100 sc-130348 in PBS, v/v, MA, USA) and anti-VEGF polyclonal antibody (Santa Cruz Biotechnology; 1:100 sc-7269 in PBS, v/v, MA, USA).…”
Section: Methodsmentioning
confidence: 99%